Properties of 249 δ Scuti Variable Star Candidates Observed During the NASA K2 Mission - Guzik, Joyce Ann; Garcia, Jorge A.; Jackiewicz, Jason (Frontiers in Astronomy and Space Sciences, 2019)
In the second phase of the NASA Kepler mission (K2), the Kepler spacecraft observed fields along the ecliptic plane for about 80 days each to search for planetary transits and monitor stellar variability. We analyzed the light curves of thousands of main-sequence stars observed as part of the Kepler Guest Observer program. Here we summarize the statistics of discovery and properties of the pulsation amplitude spectra for 249 delta Scuti variable stars or candidates observed during K2 Campaigns 4 through 17. delta Scuti variables are core or shell-hydrogen burning stars about twice as massive as the Sun, pulsating in many simultaneous radial and non-radial modes, with periods of about two hours. The growing collection of long time-series high signal-to-noise photometric data from space missions such as Kepler, combined with constraints from ground and space-based data, will be useful to constrain the interior structure of these types of variables. We hope that this list of delta Sct candidates observed by Kepler may be useful as a starting point for identifying promising targets for asteroseismic investigations.